Trends in the Social Reporting Development of Russian Companies in Terms of Digitalization - E. A. Pryadkina (Учёт. Анализ. Аудит, 2019)
Social reporting first appeared in Russia not more than two decades ago but has already become an integral part of the accounting practices of major companies. Such reporting acts as a tool for interaction between organizations and their stakeholders. With its help the entities accountable to society for the consequences of their business activity, report on environmental, social and economic consequences their companies have inflicted. While most Russian organizations are yet to develop this type of reporting, pioneer-companies are already using modern information and communication technologies in the process of disclosure of socially significant information. Their reports are becoming more and more interactive: multimedia interface allows users to customize reports themselves, transform the reports into a comfortable form for them to work with, it also allows to analyze the contained data and information, leave feedback about the content of the report and much more. Some organizations are experimenting with new channels of communication that allows them to make reports available anywhere and at any time. Such active development process of social reporting in Russia is largely defined by the normative acts, adopted in 2017: the strategy for information society development in the Russian Federation for the 2017–2030 period, the «Digital Economy» program, the concept of development of public non-financial reporting. All this suggests that the nature of social reporting development in Russia in the context of digitalization is quite progressive.